Comparison of intracervical Foley catheter combined with a single dose of vaginal misoprostol tablet or intracervical dinoprostone gel for cervical ripening: a randomised study. (17th February 2022) - Garg, Rahul; Bagga, Rashmi; Kumari, Aruna; Kalra, Jasvinder; Jain, Vanita; Saha, Subhas Chandra; Kumar, Praveen
Abstract: We compared two combined methods for cervical ripening before induction of labour (IOL) Women (n = 150) were randomised into Foley's-misoprostol (n = 75) and Foley's-dinoprostone (n = 75) groups. A single dose of vaginal misoprostol tablet (25 µg) or intracervical dinoprostone gel (0.5 mg) were used alongwith intracervical Foley's. The primary outcome was induction-delivery interval (IDI) and secondary outcomes were change in Bishop's score, oxytocin requirement, caesarean section (CS) rate, chorioamnionitis and neonatal outcome. The mean parity, gestation and indications for IOL were similar in the two groups. The IDI (19 h 37 min and 19 h 20 min; p = .683), cervical ripening time, oxytocin requirement, CS rate (18.7 and 25.4%, p = .322) and neonatal outcome were similar. Hyperstimulation developed in 2.7% women with Foley's-misoprostol and in 1.3% with Foley's-dinoprostone ( p = .55). No woman had chorioamnionitis. Thus, these two combined methods of cervical ripening and IOL were observed to be similarly efficacious. A low incidence of hyperstimulation and no chorioamnionitis may be attributed to using a single dose of prostaglandins. Misoprostol may be substituted for dinoprostone in resource limited countries. Impact statement: What is already known on this subject? Combined methods for cervical ripening (intracervical Foley's plus prostaglandins) before induction of labour (IOL) may be similarly or more efficacious than individual methods. Most studies comparing various combined methods have used repeated doses of prostaglandins. A combined method using repetitive doses of prostaglandins may increase the risk of hyperstimulation and also of infection consequent to repeated vaginal examination to administer prostaglandins. These two concerns may be offset by combining a single dose of prostaglandin with intracervical Foley's catheter. What do the results of this study add? Two combined methods for cervical ripening using a single dose of vaginal misoprostol (25 µg) or intracervical dinoprostone gel (0.5 mg) co-administered with intracervical Foley's catheter were found to be similarly efficacious. The IDI (19 h 37 min and 19 h 20 min; p = .683), cervical ripening time, oxytocin requirement, CS rate (18.7 and 25.4%, p = .322) and neonatal outcome were similar. The incidence of hyperstimulation was low (2.7 and 1.3% with Foley's-misoprostol and Foley's-dinoprostone, respectively) and no woman had chorioamnionitis. What are the implications of these findings for clinical practice and/or further research? Combined methods for cervical ripening using a single dose of prostaglandins (misoprostol or dinoprostone) were observed to be similarly efficacious. Misoprostol is a cheaper alternative to dinoprostone and may be utilised in resource limited countries. These methods may be compared with each other in more number of women in order to identify which combined method is more efficient and safe. Clinical Trials Registry of India: CTRI/2017/12/010738